ANALYSIS OF WORKLOAD, REST RIGHTS, AND THE RIGHTS TO ENJOY ENTERTAINMENT IN GENDER DIFFERENCES - Ni Putu Rai Yuliartini; Kadek Desy Pramita; Ni Luh Wayan Yasmiati (Jurnal Komunikasi Hukum, 2022)
Basically everyone agrees that women and men are different. However this has led to the position of women in the family and society below men. The assumption that women should not have a higher position that men is one of the gender inequalities that can still be felt until now. A small example of this gender inequality can be found in a family environment. The main problem in this article is the difference in workload, as well as the use of the right to the rest and the right to enjoy a consolation by each gender in a family. The type of research method used in this article is a qualitative research method. And the legal research approach used in this study is a conceptual approach. The result showed that women had greater workload than men. And women also use the right to rest and enjoyy less consolation than men.